Termination Of Household Abandonment Case Investigation - Julkipli Ritonga (UNISSULA Semarang, 2021)
In this study, the researcher will discuss the handling of cases of household abandonment at the Tabanan Police Criminal Investigation Unit with Police Report Number: LP/195/XII/2013/BALI/RES TBN About Household Abandonment, which was then stopped the investigation. In this case, neglect is carried out by a husband by leaving his wife and child for a long time without providing physical and spiritual support. This act is certainly a violation of the rights of his wife and children.An investigation was carried out on this case, but then the investigation was stopped on the grounds that there was not enough evidence with the consideration that they were having a nyentana marriage, where the women were purusa or the head of the household and the men were predana or housewives. The researcher's opinion is that it is necessary for the case to be delegated to the court level to obtain a judge's decision in order to obtain legal certainty so that later it can be used as jurisprudence for law enforcement. The theories and concepts used to analyze the problems in this study are the concept of stopping the investigation, the concept of domestic violence, the concept of customary offenses and the concept of marriage nyentana. This study uses a qualitative approach with case study research methods.